Special education leadership: leaders as motivators - Abd Aziz, Afiqah; Nordin, Mohd Norazmi; Ariff, Noredayu; Mohd Sahabuddin, Norhaflinda; Magiman, Mohamad Maulana (Turkish Online Jounal of Qualitative Inquiry, 2021)
Motivating Others To Be Better Is A Difficult Choice. A Responsible Person Wants The People Around Him To Always Be Enthusiastic In Doing Something. In The Context Of The School, Motivation Is Essential In Pursuing The Continuity Of The Best Service To The Pupils. Becoming Something More Needed When It Involves Special Education That Is Always Unique. Among The Best Motivators Other Than Students And Peers, Is From The Leadership Itself. Motivation From Them Is The Biggest Impact On Teachers. This Brief Study Was Conducted To Explore The Need For A Special Education Leader As A Motivator To Teachers. This Qualitative Study Uses Online Interviews As A Means Of Collecting Data. The Respondents Involved Consisted Of 20 Special Education Teachers In The District Of Batu Pahat, Johor, Malaysia Who Were Randomly Selected. Through The Analysis Conducted, The Findings Show That, Special Education Leaders Are The Most Important Motivators Based On Four Main Characteristics Namely Giving Advice, Being A Good Listener, Providing Enthusiasm And Close Cooperation. It Is Hoped That The Findings Of This Study Can Help The Next Researcher To Conduct Further Research.